Геоекономічна трансформація фінансово-кредитної політики агропродовольчої галузі України - Тулуш, Л. Д.; Трусова, Наталя Вікторівна; Tulush, L. D.; Trusova, Natalia (Запоріжжя : 2024, 2024)
UA:статті досліджуються трансформаційний перебіг подій щодо зміни вектору розвитку фінансово-кредитної політики агропродовольчої галузі в умовах геоекономічного простору України. Проведений детальний аналіз зовнішньої торгівлі України з ЄС та визначено видову структуру експорту продукції агропродовольчої галузі. Наведено географічну структуру фінансової системи України за рівнем забезпечення суб’єктів агропродовольчої галузі України власними заощадженнями. Розраховано вплив валютних ризиків на експорт зернових культур в середньому на одного суб’єкта агропродовольчої галузі України. Представлено структуру джерел формування фінансово-кредитної системи агропродовольчої галузі України міжнародними фінансовими інститутами в період воєнного стану. Визначено особливі умови функціонування агропродовольчій галузі в інституціональній структурі фінансових потоків міжнародних фінансових інститутів для відтворення монетарних, бюджетних, податкових стимулів країни. EN: Abstract. The article examines the transformational course of events regarding the change in the direction of the development of the financial and credit policy of the agro-food industry in the context of changes in the institutional doctrine of Ukraine. The direction of changes in the development of the financial and credit policy of the agro-food industry of Ukraine with the aim of suspending the monetary, banking and budget recession, restoring economic ties with the EU during the period of martial law, establishing temporary support and activating the movement of financial flows from global financial institutions are substantiated. A conceptual approach to changing the institutional doctrine of Ukraine and the development of the financial and credit policy of the agro-food industry with the help of four interconnected sectors is presented: private, budgetary, monetary and foreign economic. The trend of changes in the NBU discount rate in the prewar and wartime period of Ukraine, which is closely related to the overnight rates on the interbank market, is given. The amount of lending to the agro-food industry under the state program “Affordable loans 5-7-9%” is given and its interaction with portfolio guarantees of banking institutions is proven. The structure of grant aid to agro-food industries from international financial institutions is presented. The promising direction of financial inclusion and restoration of the agro-food industry should be a transformational model of the general balance of financial and credit flows between the countries of the European Union and Ukraine. A special institutional structure of finance in the agro-food industry is defined, which forms the movement of financial flows from international financial institutions for the reproduction of monetary, budgetary and tax incentives in a new vector of the country's development.
Geoeconomic transformation of the financial and credit policy of the agricultural industry of Ukraine
Keywords: фінансово-кредитна політика; агропродовольча галузь; банківське кредитування; фінансова підтримка; гранти; фінансові інститути; financial and credit policy; agro-food industry; bank lending; financial support; grants; financial institutions